(untitled) (Tamaddun, 2019)
Abstract In order to cultivate the kind of technology literacy in our students called for by leaders in the field, it must simultaneously be cultivated in our teachers. While the literature in the field of English education demonstrates the efficacy of computer technology in writing instruction and addresses its impact on the evolving definition of literacy in the 21st century, it does not provide measured directions for how English teachers might develop technology literacy themselves or specific plans for how they might begin to critically assess the potential that technology might hold for them in enhancing instruction. This article presents a pedagogical framework encompassing the necessary critical mindset in which teachers of the English language arts can begin to conceive their own "best practices" with technology—a framework that is based upon their needs, goals, students, and classrooms, rather than the external pressure to fit random and often decontextualized technology applications into an already complex and full curriculum. To maximize technology’s benefits, educators must develop a heightened, critical view of technology to determine its potential for the classroom.